Model Pembelajaran Kooperatif Tipe Inside-Outside Circle dalam Pembelajaran Bilingual Terhadap Hasil Belajar Siswa - Noge, Maria Desidaria; Tegu, Yohana Ivantiana; Kaka, Pelipus Wungo (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2020)
This research aims at finding out the differences in thematic learning achievement between students who learned by using Inside-Outside Circle cooperative learning model in Bilingual learning and direct learning model in class IV of group I of West Golewa Subdistrict, Ngada Regency. The research Â method used a quantitative research with a true experimental research of Posttest-only Control Group Design. This research was conducted at class IV students of Group I of West Golewa Subdistrict, with sample totaled 34 students. The data collection technique used post-test in the form of multiple choices test. The result of post-test was then analyzed using the t-test technique. Based on the data of tcount = 4.797 and ttable with significance level of 5% (É‘ = 0.05) = 2,021. Because of tcount 4,797 > ttable 2,021, then Ho was rejected and H1 was accepted. The result proved that the experimental class using the Inside Outside Circle in Bilingual learning model was higher than the control class (85.12 > 65.47). Therefore, it can be concluded that there are differences in thematic learning achievement between the experimental group and the control group and the Inside Outside Circle learning model based Bilingual learning towards students learning achievement.